Effect of Genex, a feed additive containing organic acids and herb extracts, on the performance of broiler chickens - SPAIS (A.B. ΣΠΑΗΣ), A. B.; GIANNENAS (Η.Α.ΓΙΑΝΝΕΝΑΣ), I. A.; FLOROU-PANERI (Π. ΦΛΩΡΟΥ-ΠΑΝΕΡΗ), P.; CHRISTAKI (Ε ΧΡΗΣΤΑΚΗ), E.; BOTSOGLOU (Ν.Α. ΜΠΟΤΣΟΓΛΟΥ), N. A. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this experimental study, the performance of broiler chickens fed diets supplemented with Genex, a feed additive containing organic acids and their ammonium salts, essential oils and plant extracts, was evaluated. A total of 17,340 one day-old Cobb chicks randomly divided into three groups and housed in floor pens of a commercial farm, were used in a feeding trial that lasted 40 days. One group was fed on a basal commercial diet, the second group on the same diet supplemented with 8 g flavomycin /ton of feed, while the third group was given the basal diet supplemented with Genex at 3 kg/ton till 21 days of age and 4 kg/ton thereafter. In this trial the buffering capacity of the tested diets and their ingredients was also measured. Results based on the body weight growth, the feed conversion ratios, the mortality rate and the productivity index suggested that supplementation of the feed with Genex exerted a growth-promoting effect comparable to that of flavomycin.